Efficacy and safety of transcranial direct current stimulation for post-stroke spasticity: A meta-analysis of randomised controlled trials. (February 2022) - Huang, Jiapeng; Qu, Yun; Liu, Lini; Zhao, Kehong; Zhao, Ziqi
Objectives: To evaluate the efficacy and safety of transcranial direct current stimulation for post-stroke spasticity and to assess its evidence using a meta-analysis. Methods: We searched the Cochrane Library, EMBASE, MEDLINE (via PubMed), PEDro, CBM, CNKI and Wan Fang Data from their inception to June 2021 for randomised clinical trials published in English or Chinese, which aimed to explore the effects of transcranial direct current stimulation on post-stroke spasticity. Two reviewers independently extracted the data and evaluated the methodological quality and overall evidence quality. Results: Thirteen randomised clinical trials comprising 924 patients were included, 12 of which were included in the meta-analysis. The results showed that anodal stimulation (standard mean difference = −0.91; [95% CI; −1.63 to −0.19]) combined with other therapies was more effective in improving upper limb spasticity. More than 20 minutes of stimulation were found to be effective in improving spasticity. Transcranial direct current stimulation was superior to the control treatments for subacute (standard mean difference = −1.16; −1.75 to −0.57) and chronic stroke (standard mean difference = −0.68; −1.13 to −0.22) patients aged under 60 (standard mean difference = −1.07; −1.54 to −0.60). No severe adverse events were reported in any of the included studies. Conclusions: Low-quality evidence demonstrates that anodal transcranial direct current stimulation as an adjunct is effective and safe in reducing upper limb post-stroke spasticity when applied for more than 20 minutes in subacute and chronic stroke survivors aged under 60. Further high-quality studies are needed to explore its long-term efficacy and safety.